Thermal Visualization and Performance Analysis in a Channel Installing Transverse Baffles with Square Wings - Eiamsa-Ard, Smith; Phila, Arnut; Wongcharee, Khwanchit; Chuwattanakul, Varesa; Pimsarn, Monsak; Maruyama, Naoki; Hirota, Masafumi (My University, 2022)
The experimental examination of local heat transfer, thermal intensification, friction factors, and thermal performance factors (TPF) in a rectangular channel with square-winged transverse baffles (SW-TB) are presented in this paper. The purpose of this study is to modify the typical transverse baffles (TB) into square-winged transverse baffles (SW-TB) in order to improve the thermal performance and heat transfer rate of the channel. The effects of SW-TBs with various wing attack angles and Reynolds numbers on the heat transfer performance characteristics were examined using a thermochromic liquid crystal sheet. In the experiments, the SW-TBs were attached to the bottom wall of the channel, which had an aspect ratio (W:H) of 3.75:1. The SW-TBs had a width (w) of 150 mm, a square perforated cross-sectional area (a × b) of 8 × 8 mm2, and attack angles (θ) of 0° (solid transverse-baffle), 22.5°, 45°, 67.5°, and 90°. The bottom wall of the channel was evenly heated, while the other walls were insulated. The temperature contours on the heated surface were plotted using temperatures obtained through using the thermochromic liquid crystal (TLC) image-processing method. Experimental results revealed that the SW-TBs created multiple impinging jets, apart from the recirculation. At the proper attack angles (θ = 22.5° and 45°), the SW-TBs offered greater heat transfer rates and caused lower friction losses, resulting in higher TPFs than the solid transverse baffles. In the current work, channels where the SW-TBs display a θ = 45° presented the greatest TPF, as high as 1.26. The multiple impinging jets issuing by the SW-TBs suppressed the size of the recirculation flow and allowed better contact between the fluid flow and channel wall.
Keywords: channel; heat transfer; square-winged transverse baffles; thermal performance